Revolutionizing Healthcare in India: Impact of Clinical Pharmacists in Enhancing Patient Outcomes - Chauhan, Vishal; Shah, Maitri; Shah, Kashvi; Gupta, Yogesh (Indian Journal of Pharmacy Practice)
During the past few years, the pharmacy profession has expanded significantly in delivering professional services and plays an integral role in the multidisciplinary provision of health care. The traditional role of pharmacists is expanding and now pharmacists are playing a role as a vital team member in the direct care of patients. Over the past few years, the clinical pharmacy has expanded its professional services significantly, leading to the introduction of the Doctor of Pharmacy study program. The aim of this paper is to highlight the role of clinical pharmacists in various departments. Clinical pharmacists are professionals with specialized training that offer complete drug management and direct patient care. The role of clinical pharmacists involves ward round participation, medical review of patient data, minimizing drug interactions and adverse events and patient counselling, thus enhancing the patient safety. The clinical pharmacists are mainly responsible for the Pharmacy and Therapeutics committee and Antibiotic stewardship program of hospital. Thus, in collaboration with doctors, nurses, and pharmacists, clinical pharmacists improve patient outcomes.
Keywords: Clinical Pharmacist; Doctor of Pharmacy; Pharmacy Practice; Clinical Pharmacy Services; India